Impact of religion affiliation and religiosity on consumer innovativeness; the evidence of Malaysia - Mansori, Shaheen (IDOSI Publications, 2012)
Introducing new product to the market is the only way to create sustainable competitive advantage. However, the success of any product/service in market is ultimately depended on consumer acceptance. Innovativeness is one of the individual characteristics that might influence the acceptance of novel product/services. Innovativeness itself also from other side might be affected by several factors such individual’s religion affiliation and the level of commitment to his/her religion. This study tested the effect of religiosity on innovativeness to explore disparities between devote and casual religions’ followers. Moreover, the relationship between religion affiliation and innovativeness was studied. The results showed that religiosity has negative impact on innovativeness. Furthermore, the result indicated that Buddhists have significantly lower innovativeness compared to Muslims, Christians and Hindus in Malaysia.